Alpha-Synuclein Post-translational Modifications: Implications for Pathogenesis of Lewy Body Disorders - Manzanza, Nelson de Oliveira; Sedlackova, Lucia; Kalaria, Raj N. (Frontiers in Aging Neuroscience, 2021)
Lewy Body Disorders (LBDs) lie within the spectrum of age-related neurodegenerative diseases now frequently categorized as the synucleinopathies. LBDs are considered to be among the second most common form of neurodegenerative dementias after Alzheimer's disease. They are progressive conditions with variable clinical symptoms embodied within specific cognitive and behavioral disorders. There are currently no effective treatments for LBDs. LBDs are histopathologically characterized by the presence of abnormal neuronal inclusions commonly known as Lewy Bodies (LBs) and extracellular Lewy Neurites (LNs). The inclusions predominantly comprise aggregates of alpha-synuclein (aSyn). It has been proposed that post-translational modifications (PTMs) such as aSyn phosphorylation, ubiquitination SUMOylation, Nitration, o-GlcNacylation, and Truncation play important roles in the formation of toxic forms of the protein, which consequently facilitates the formation of these inclusions. This review focuses on the role of different PTMs in aSyn in the pathogenesis of LBDs. We highlight how these PTMs interact with aSyn to promote misfolding and aggregation and interplay with cell membranes leading to the potential functional and pathogenic consequences detected so far, and their involvement in the development of LBDs.